2023
DOI: 10.1038/s41597-023-02033-1
|View full text |Cite|
|
Sign up to set email alerts
|

First assessment of underwater sound levels in the Northern Adriatic Sea at the basin scale

Abstract: The protection of marine habitats from human-generated underwater noise is an emerging challenge. Baseline information on sound levels, however, is poorly available, especially in the Mediterranean Sea. To bridge this knowledge gap, the SOUNDSCAPE project ran a basin-scale, cross-national, long-term underwater monitoring in the Northern Adriatic Sea. A network of nine monitoring stations, characterized by different natural conditions and anthropogenic pressures, ensured acoustic data collection from March 2020… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…This work encourages the collection of broadband acoustic to provide context to detector performances and the ambient environment in which the animals are residing. As marine habitats get noisier a range of national and international regulations 35,36,37 have arisen to understand and quantify noise levels regionally. Using a CNN as part of the analysis pipeline allows automated signal extraction to occur in a timely manner and encourages researchers to gather large PAM datasets which can be used to address a wealth of ecological questions.…”
Section: Discussionmentioning
confidence: 99%
“…This work encourages the collection of broadband acoustic to provide context to detector performances and the ambient environment in which the animals are residing. As marine habitats get noisier a range of national and international regulations 35,36,37 have arisen to understand and quantify noise levels regionally. Using a CNN as part of the analysis pipeline allows automated signal extraction to occur in a timely manner and encourages researchers to gather large PAM datasets which can be used to address a wealth of ecological questions.…”
Section: Discussionmentioning
confidence: 99%
“…In Croatian waters, noise caused by boat traffic is known to affect dolphin whistle frequencies (Rako-Gospić and Picciulin, 2016) and one study showed a significant seasonal displacement of dolphins from areas with intense traffic of leisure boats (Rako et al, 2013a). In recent years, extensive underwater acoustic data in the northern and central Adriatic Sea were recorded in the context of project SOUNDSCAPE, and this effort has provided baseline information on sound levels (Petrizzo et al, 2023;Picciulin et al, 2023), useful to assess acoustic threats to marine life including cetaceans.…”
Section: Effects Of Anthropogenic Noisementioning
confidence: 99%
“…Typically, a measurement period lasted 3 months, after which each recorder needed to be recovered to download data and to remove biological fouling. The SOUNDSCAPE measurement period covers 16 months (from 1 March 2020 to 30 June 2021); the data coverage per each monitoring station is represented by Figure S1 (Supplementary Materials) and it is described in detail by 23 .…”
Section: Data Acquisition and Data Coveragementioning
confidence: 99%
“…Other stations, however, were in proximity to important conservation areas like Natura 2000 sites (Parco del Conero, Italia, MS3, and Losinj archipelago, Croatia, MS6) or sh reproductive areas (Žirje, Croatia; MS7). This study aims to describe the spatial and temporal variations in the NAS ambient sound pressure levels over one year period, on the base of the recently released dataset 23 and to discuss the results in the light of available literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation